Mastering the potter's wheel techniques, tips, and tricks for potters - Carter, Ben 1980- (Voyageur Press, 2016)
"A book of advances wheel techniques and inspiration for potters who have basic skills but would like to learn more about throwing large forms, lids, handles, darting, and more"-- Provided by publisher.